2022
DOI: 10.1097/prs.0000000000008824
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chemotherapy and Radiation Therapy on Inflammatory Response, Neovascularization, and Capsule Formation of Acellular Dermal Matrix in Breast Reconstruction: Analysis of the BREASTrial Biopsy Specimens

Abstract: Background: The Breast Reconstruction Evaluation of Acellular Dermal Matrix as a Sling Trial is a single-center, blinded, prospective, randomized, controlled trial established to compare outcomes using two popular types of acellular dermal matrices, AlloDerm and DermaMatrix, in tissue expander breast reconstruction. This study used the acellular dermal matrix biopsy specimens from the trial to evaluate how adjuvant therapy influences inflammation, neovascularization, and capsule formation of the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…1,2 Supporting this potential limitation are the histologic results from the BREASTrial biopsy specimens, which showed that groups of patients who underwent reconstruction with DermaMatrix experienced less of an inflammatory response compared to those who underwent reconstruction with AlloDerm. 6 Obesity was a reliable predictor of developing a complication, regardless of acellular dermal matrix type or reconstruction method. This finding is consistent with findings from stage II.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…1,2 Supporting this potential limitation are the histologic results from the BREASTrial biopsy specimens, which showed that groups of patients who underwent reconstruction with DermaMatrix experienced less of an inflammatory response compared to those who underwent reconstruction with AlloDerm. 6 Obesity was a reliable predictor of developing a complication, regardless of acellular dermal matrix type or reconstruction method. This finding is consistent with findings from stage II.…”
Section: Discussionmentioning
confidence: 92%
“…This trial specifically supports two-stage reconstruction as a safe approach, as the overall complication rates were low among our cohort and histologic results were similar between acellular dermal matrices. 6 Ultimately, patient preference and surgeon expertise should be used during preoperative planning, as both approaches have benefits and drawbacks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although the submuscular ADM-assisted technique is now extensively documented, the choice of reconstruction materials should always be evaluated, updating clinical practice with increasingly extensive follow-ups. Furthermore, in the current broad panorama of reconstruction-declined devices, different materials may lead to different outcomes: source, preparation, and thickness of acellular dermal matrices may influence the development of post-operative complications [ 25 ]. Therefore, each device should be investigated individually and independently.…”
Section: Discussionmentioning
confidence: 99%
“…Why is the capsular contracture rate the same for complete implant ADM coverage versus only anterior coverage as seen in the authors' study, and what is the histologic difference of capsule formation on pectoralis fascia versus ADM? Although ADM does seem to mitigate some of the effects of postoperative radiation therapy as the authors note, [15][16][17][18] can we develop additional techniques in addition to fat grafting 19,20 to further modify the effects of radiation therapy? Does complete wraparound coverage give better protection from radiation than just anterior coverage?…”
mentioning
confidence: 99%